Surgical treatment of vaginal prolapse - Bedoya Hevia, Mariano (2015)
To address the issue of surgical treatment of genital prolapse is imperative to refer to the values of the different anatomical structures that focus on the basic principle that surgical techniques are based to bring the prolapsed organs to their normal position.